P202 Outlasting effect of transcranial alternating current stimulation (tACS) on individual alpha power decays within 90 min after stimulation. Issue 3 (March 2017) - Kasten, F.H.; Dowsett, J.; Herrmann, C.S.
Abstract : Introduction: Transcranial alternating current stimulation (tACS) has been shown to modulate spontaneous brain activity in a frequency specific manner (Herrmann et al., 2013 ). Numerous studies reported outlasting effects of tACS for different frequencies and stimulation protocols which commonly exceeded the duration of the experiment (Veniero et al., 2015 ). In the alpha band the effect has been shown to last for at least 30 min (Neuling et al., 2013 ). However, the further development and total duration of the aftereffect remain unclear. Objectives: The present study aimed to determine total duration and development of the tACS aftereffect beyond the previously reported 30 min. Materials & methods: Seventeen subjects received either 20 min of tACS or sham stimulation at their individual alpha frequency (IAF) using a Cz-Oz montage. EEG was measured during 3 min before and 90 min after tACS, while participants performed a visual vigilance task. Results: IAF band power (IAF ± 2 Hz) was increased in the verum group compared to baseline and sham for 70–80 min after stimulation. While alpha power in the verum group did not return to baseline, the group difference between verum and sham decayed due to an alpha power increase in the sham group. Conclusion: The current findings replicated previous observations of an aftereffect of tACS and for the first time demonstrated an upper limit for the duration of this aftereffect when compared to sham. Furthermore, the overall alpha rise over time for both groups emphasizes the importance of a carefully chosen definition of the aftereffect and its reference (baseline or sham condition).